2012
DOI: 10.1016/s1734-1140(12)70731-4
|View full text |Cite
|
Sign up to set email alerts
|

Sub-chronic exposure to noise affects locomotor activity and produces anxiogenic and depressive like behavior in rats

Abstract: Noise is defined as a displeasing and unwanted sound. It is one of the most encountered stressor to which mankind is exposed. Frustration, poor reading, impaired hearing and difficulty in problem solving activities are the common consequences of noise stress. It has been reported to produce atrophy of dendrites and alterations in neurotransmitter levels. Long term exposure to inescapable noise stress induces exhaustion, defeat, annoyance followed by decreased muscle movement, social contacts and mood changes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
50
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 22 publications
8
50
2
Order By: Relevance
“…In this study, noise stress resulted in increase in immobility time in the TST, which is in line with the previous reports in which exposure to sub-chronic noise and loud tones of noise produced depressive-like behavior in the rodent TST and forced swimming test [9,10]. In this respect, Naqvi et al [9] showed that 15 days of noise exposure (4 h per day, at 100 dB) to rat significantly increases immobility behavior of animals in the TST. Given this, observed despair and longer immobility activity in the current study could be due to the change in serotonin and dopamine concentrations following noise exposure.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, noise stress resulted in increase in immobility time in the TST, which is in line with the previous reports in which exposure to sub-chronic noise and loud tones of noise produced depressive-like behavior in the rodent TST and forced swimming test [9,10]. In this respect, Naqvi et al [9] showed that 15 days of noise exposure (4 h per day, at 100 dB) to rat significantly increases immobility behavior of animals in the TST. Given this, observed despair and longer immobility activity in the current study could be due to the change in serotonin and dopamine concentrations following noise exposure.…”
Section: Discussionsupporting
confidence: 93%
“…Studies in animal models showed that decrease in the release of serotonin and dopamine results in immobility behavior in the TST [16,17]. In this study, noise stress resulted in increase in immobility time in the TST, which is in line with the previous reports in which exposure to sub-chronic noise and loud tones of noise produced depressive-like behavior in the rodent TST and forced swimming test [9,10]. In this respect, Naqvi et al [9] showed that 15 days of noise exposure (4 h per day, at 100 dB) to rat significantly increases immobility behavior of animals in the TST.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Noise exposure also affects animals' emotional state; for example, in humans it generates depression and aggression (Ising & Kruppa 2004, Stansfeld 2003 and in rats it results in anxiety and depression (Naqvi, et al 2012). In pandas, noise exposure increased urinary corticoids, locomotion, distress vocalizations and escape attempts (Owen, et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…transportation noise has been extensively studied (see, for example, Barber, et al rats, sub-chronic noise exposure (4 h, 100 dB for 15 days) produces anxiety and 142 depressive behaviours evaluated through an elevated plus-maze (Naqvi, et al 2012); in 143 pandas, exposure to approximately 72 dB ambient noise is related to increased urinary 144 corticoids, locomotion, distress vocalizations and escape attempts (Owen, et al 2004 Based on the characteristics of mining noise described in the literature (Camargo,et al 229 2009, Nanda, et al 2009, Nanda, et al 2011, Pathak, et al 1999 behaviours for pairs of females were analysed as the means of the two animals per cage.…”
mentioning
confidence: 99%